Numerical Comparison of Triangular and Sinusoidal External Vibration Effects on the 3D Porous Drying Process - Ben Khedher, N.; Ramzi, R.; Alatawi, I. A. (Engineering, Technology & Applied Science Research, 2020)
Drying is one of the most energy-intensive industrial processes. One of the techniques aiming to reduce energy consumption is the vibration technique which is generally employed to intensify the heat and mass transfer process. In this respect, this paper presents a three-dimensional numerical model to study the external vibration effects on the drying process of a porous medium. The model is based on a comparison of heat and mass transfer phenomena that arise during vibrating drying of unsaturated porous medium for two cases: triangular and sinusoidal external vibrations. The three-dimensional unstructured Control Volume Finite Element Method (CVFEM) is employed to simulate the vibrating drying. Numerical results of the time evolution of temperature, liquid saturation, pressure, and water content are compared and analyzed for the two cases.